Ecofriendly Perovskites with Giant Self‐Defocusing Optical Response. Issue 2 (21st November 2022) - Suárez, Isaac; Martínez‐Pastor, Juan P.; Oszajca, Marek F.; Lüchinger, Norman A.; Graves, Brian; Agouram, Said; Milián, Carles; Ferrando, Albert
Abstract: The full optical control of light using sustainable green technologies is one of the incipient challenges of the Photonics community. There are, however, few optical materials able to provide a significant nonlinear refractive index change under small enough intensities (< 1 GW cm −2 ), and, more importantly, allowing the external control of the magnitude and sign of their nonlinear response. This manuscript demonstrates that Cs2 SnI6 lead‐free nanocrystals (NCs) present an extraordinary self‐defocusing response not yet observed up to now in any material. Despite its complex structural form, these NCs are fully characterized here, both experimentally and theoretically, revealing a giant negative refractive change Δ n = −0.05 under proper illumination conditions. The nonlinear response is tuned with the intensity, concentration of NCs in the solvent, and propagation distance leading to a crossover where the media transforms to self‐focusing with Δ n = +0.002. These results can provide fascinating opportunities in sensing and light–matter interactions for a future ecofriendly photonic technology. Abstract : Ecofriendly Cs2 SnI6 lead‐free nanocrystals (NCs) present an extraordinary self‐defocusing response. The complex nonlinearity is fully determined, theoretically and experimentally, and indicates that the refractive index change follows a phase diagram with the intensity and concentration of NCs in the solvent. These results can open new routes in nonlinear photonics not possible until now.